Development of Basic Analysis of Prose Coursebook Containing Critical Theories at a State University in Karawang - Kriswanda Krishnapatria (ENGLISH EDUCATION DEPARTMENT - UNIVERSITAS SINGAPERBANGSA KARAWANG, 2019)
This research is motivated by the need of textbook used in the process of literature lecturing, especially prose. Critical theories discourse contained in literary work can be an interesting issue when textbooks used in Higher Education have not provided a mandate and a good and strong model to imitate. Given the importance of the role of textbooks in the process of knowledge transfer other than lecturers, it is necessary to develop literary coursebooks that subtly contain critical theories in order to produce better quality resources in changing attitudes and actions of readers.This research used a simplified Research and Development method that only covered three main stages: (1) preliminary study, (2) product formulation and development, and (3) product validation and dissemination. In addition, this study focused on coursebooks containing critical theories for English Education students of 6th Semester on Basic Analysis of Prose course at State University of Singaperbangsa Karawang.The coursebook as the development product for Basic Analysis of Prose in English Language Education Program at State University of Singaperbangsa Karawang has a total average analysis of validation results and small group testing above 80%, so it can be categorized as valid and feasible.